How does Family Socioeconomic Status influence Children's Cardinality Principle? The chain mediation roles of Approximate Number System and Receptive Vocabulary Skills - Huanhuan Li; Yifang Wang; Bingyu Duan; Qiaoke Kuang; Xinxin Guo; Enwei Xu (Frontiers in Psychology, 2025)
BackgroundFamily Socioeconomic Status, the Approximate Number System, and the Receptive Vocabulary Skills have been identified as key factors influencing the development of children's Cardinality Principle. However, the relationships among these variables and their underlying mechanisms remain unclear. This study aims to investigate how the Family Socioeconomic Status (FES) impacts children's understanding of the Cardinality Principle, with a focus on the mediating roles of the Approximate Number System (ANS) and the Receptive Vocabulary Skills (RVS).MethodsA cross-sectional design was employed, involving 110 children (55 boys, 55 girls; Mean age = 67.53 months, SD = 7.415 months) and their parents. Parents provided information on the Family Socioeconomic Status (income, education level, and occupation). Children's performance on the Approximate Number System, the Receptive Vocabulary Skills, and the Cardinality Principle (CP) tasks was assessed using the Panamath software, the Peabody Picture Vocabulary Test - Revised (PPVT- R), the “How Many” task, and the “Give-N” task. Data were analyzed using SPSS 29.0 and PROCESS v4.1 (Model 6).ResultsCorrelation analyses revealed significant positive associations between children's Cardinality Principle, Family Socioeconomic Status, Approximate Number System, and Receptive Vocabulary Skills. After controlling for child gender and age, mediation analysis indicated that the Family Socioeconomic Status had a direct positive effect on children's Cardinality Principle. The Approximate Number System and the Receptive Vocabulary Skills each partially mediated the relationship between Family Socioeconomic Status and Cardinality Principle. Additionally, the Approximate Number System and the Receptive Vocabulary Skills together acted as chain mediators in the Family Socioeconomic Status- Cardinality Principle relationship.ConclusionsThis study highlights that the Family Socioeconomic Status indirectly influences the development of the Cardinality Principle through the Approximate Number System and Receptive Vocabulary Skills, underscoring the complex interactions between the Family Socioeconomic Status, the Approximate Number System, and Receptive Vocabulary Skills in the development of children's mathematical abilities. The findings suggest that early educational interventions should consider both cognitive and language development alongside socioeconomic factors to better support children's mathematical learning.